20 Years of brand personality: a bibliometric review and research agenda. Issue 4 (July 2018) - Radler, Viktoria
Abstract This article aims to deconstruct 20 years of research on brand personality by systematically reviewing the extant literature and identifying relevant research gaps. The current status of brand personality research is analyzed by applying bibliometric co-citation meta-analysis. This interdisciplinary review includes 220 articles in 62 journals from theISI Web of Science . A total of 8108 citations were used to discuss key contributions, underlying research streams, journal outlets and to point out future directions of the field. Based on the citation map, five research clusters within brand personality literature were identified:Measurement of Brand Personality ;Direct and Indirect Effects of Brand Personality ;Dynamics of Brand Personality Dimensions ;Brand Personality in Brand Extensions ; andApplication of Brand Personality to Related Areas . Furthermore, a set of research questions is proposed to be considered for future research. Thus, the study provides a relevant interdisciplinary platform on brand personality research for academics and practitioners and stimulates the development of further knowledge on this topic.